2015
DOI: 10.17221/8076-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breeder age and lighting regimen on growth performance, organ weights, villus development, and bursa of fabricius histological structure in broiler chickens

Abstract: ABSTRACT:This study was carried out to investigate the effect of breeder age and lighting regimen on performance, some organ weights, villus development, and bursa of fabricius histological structure in broiler chickens. A total of 384 one-day-old chicks were obtained from two Ross broiler breeder flocks at 32 (young;Y) and 49 (old, O) weeks of age. Chicks from each breeder age were reared under 18 h light : 6 h dark (18 L : 6 D) (control; CL) or 14 L : 4 D : 2 L : 4 D (split darkness, SD). Body weight, feed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…However, the present findings shown in Table 6 indicated that these immune organs (bursa of Fabricius and the spleen) were not significantly correlated in young birds (up to 10 days). In this sense, the bursa of Fabricius has been reported to grow at a circadian rate higher than the spleen in the early days of birds [ 53 ]; ( Figure 1 ), since the greatest activity of the spleen as a secondary lymphoid organ occurs in adult birds. However, Perozo et al [ 21 ] reported a correlated association between thymus and spleen; similar results are seen in Table 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present findings shown in Table 6 indicated that these immune organs (bursa of Fabricius and the spleen) were not significantly correlated in young birds (up to 10 days). In this sense, the bursa of Fabricius has been reported to grow at a circadian rate higher than the spleen in the early days of birds [ 53 ]; ( Figure 1 ), since the greatest activity of the spleen as a secondary lymphoid organ occurs in adult birds. However, Perozo et al [ 21 ] reported a correlated association between thymus and spleen; similar results are seen in Table 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Perozo et al [ 21 ] reported a correlated association between thymus and spleen; similar results are seen in Table 6 . Likewise, the liver, spleen, and heart have a positive correlation due to hepatic portal blood circulation; the venous blood that arises from the gastrointestinal organs and the spleen is rich in the digestive substance’s tract [ 53 , 54 ]. These results coincide with Philipsen et al [ 55 ], who showed a positive correlation between the liver and heart, as they connected through the portal vein, which contributes to the detoxification and exchange of arterial blood.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the effect of breeder age, Ipek and Sözcü (2015) reported a higher body weight at 7 D of age with younger flocks (33 vs. 62 wk) and explained this result by the higher yolk sac absorption and the advanced intestinal development in hatchlings of the young flock. However, Sabry et al. (2015) noted a higher body weight at 35 D of chicken age with older breeders (49 vs. 32 wk).…”
Section: Introductionmentioning
confidence: 86%
“…Artificially incubated eggs are influenced by the temperature, ventilation, humidity, and turning that allow tissue growth, extraembryonic membrane development, gas exchange, and moisture loss (Decuypere and Michels, 1992;French, 1997;Molenaar et al, 2010;Boleli et al, 2016). However, the optimum parameters for all embryos in a machine are not the same due breeder genetics and age, egg composition and yolk size, eggshell and albumen properties, storage time and temperature of storage, among other factors (Molenaar et al, 2010;Yalçin et al, 2014;El Sabry et al, 2015;Nangsuay et al, 2017;Okur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%